Stepwise rapid electrolytic synthesis of graphene oxide for efficient adsorption of organic pollutants. Issue 12 (6th March 2023) - Xu, Wanzhen; Zhu, Wenjie; Shen, Junliang; Kuai, Mingyue; Zhang, Yi; Huang, Weihong; Yang, Wenming; Li, Mengmeng; Yang, Sheng
Abstract : A stepwise intercalation and electrochemical oxidation method has been developed for the rapid synthesis of graphene oxide (GO). Such heavily oxidized GO sheets demonstrate great efficiency for the adsorption of methylene blue in water. Abstract : Graphene oxide (GO) has been widely used in energy devices, biomedicine, environmental protection, composite materials and other fields. Hummers' method is currently one of the most powerful strategies for the preparation of GO. However, many deficiencies, including severe environmental pollution, operation safety issues and low oxidation efficiency are major obstacles for the large-scale green synthesis of GO. Here, we report a stepwise electrochemical method for the fast preparation of GO using spontaneous persulfate intercalation followed by anodic electrolytic oxidation. Such a step-by-step process not only avoids uneven intercalation and insufficient oxidation in traditional one-pot methods, but also largely shortens the overall duration by two orders of magnitude. In particular, the oxygen content of the obtained GO is as high as 33.7 at%, almost double that from Hummers' method (17.4 at%). The abundant surface functional groups render this GO an excellent adsorption platform for methylene blue with an adsorption capacity of 358 mg g −1, 1.8-fold higher than conventional GO.